Contribution to the identification of morphological descriptors for the genetic diversity of argan tree (Argania spinosa L. Skeels) - Alfred Balenor Buernor; Ahmed Amri; Ahmed Birouk; Chafik Analy; Zakaria Kehel; Abderrahmane Aitlhaj (Global Journal of Ecology - Peertechz Publications, 2021)
The argan tree (Argania spinosa L. Skeels) is a species of great ecologic, economic and social importance in Morocco. It is a multi-purpose tree supporting the livelihoods of rural communities in the south-west parts of the country with increasing interest in using its oil in cosmetics and pharmaceutical industries. The anthropological overuse combined with parasitic attack and recurrent droughts contribute to the rapid degradation of its ecosystem. The efficient in situ conservation of the argan tree and its ecosystem as well as breeding efforts for the domestication of this species require the development of descriptors for the characterization of the diversity and identification of the argan tree. This work aims to contribute to the identification of key descriptors of the argan tree using qualitative characteristics related to tree shapes, twigs, leaves, fruits, and seed as well as quantitative measures of these same organs. A total of 255 trees were sampled at four sites in four provinces, namely: Agadir, Essaouira, Sidi Ifni and Ait Baha. A total of thirty-one characteristics were assessed. The results showed a high morphological diversity for many of both qualitative and quantitative characteristics at all sites. However, the frequencies of the different classes and the share of variance for each trait vary across sites. The qualitative characteristics were more discriminant especially the shape of the fruit, the shape of the leaves, the leaf surface, the shape of the tree and the colour of the leaves are very variable and have a strong contribution to explanation of the diversity of the argan tree. The leaf area, seed area, number of carpels, density of spines, and branch length explain nearly 42% of the diversity and can serve as descriptors of argan tree diversity which can help in the efficient conservation of the argan ecosystem and in the selection and protection of clones for the promotion of arganiculture.